The Opinions of Agricultural Extension Agents in the Agricultural Extension Problems in Jordan and its Relation to Certain Factors - AL-Shadiadeh, Ahmad N.; Alkharabsheh, Fatima A.H. (Jordan Journal of Agricultural Sciences, 2019)
This study aims to determine the opinions of agricultural extension agents in Jordan in agricultural extension problems and to study the relationship between the opinions and some variables such as personal and professional characteristics of agricultural extension agents. Data were collected from 61 extension agents through by personal interview through a questionnaire that included two parts; the first was the personal and professional information of the extension agents and the second was a measure of their opinions on the agricultural extension problems in Jordan. To achieve research objectives, the Likert scale was used (strongly agree, agree, neutral, not agree, and strongly disagree) to measure opinions of agricultural extension agents through thirty-eight paragraphs distributed on eight axes related to the extension problems in Jordan. For analyzing data, frequencies, percentages, mean standard deviations, Pearson and Spearman correlation, and chi-square. The most important results of the study are: There were three categories for these opinions: negative opinions (<142) points, Neutral opinions (142-152) points, and Positive opinions (> 152) points. It was found that 24.6%, 54.1%, and 21.3% of extension agents were found in these above categories, respectively. Ranking of the problems of the agricultural extension came according to the following descending sequence: the agricultural extension philosophy, the institutional problems, technical problems, training problems, management problems, social problems, legislative problems, and environmental problems, where the relative importance of their averages was 84%, 82 %,82 %, 72.2%, 72 %, 71 %, 65 %, and 49 %, respectively. From the results, a significant association was observed between the characteristics such as gender, service years in the agricultural ministry, and work territory. On the other hand, no signs were found related to age, education level, service years in the agricultural extension, job title, and training courses. Thus, this study recommends that agricultural extension must take an extra role for education and awareness by agricultural extension agents and dissemination of knowledge through a scientific and practical plan that includes simplifying the results according to the opinions of agricultural extension agents in jordan.